Analysis of Factors Affecting the Utilization of Outcome Services at Prima Husada Hospital Malang - Lilik Afifah; Yuly Peristiowati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
In 2019 to 2021 there was a very high increase in outpatient visits at the Hospital of Prima Husada. In 2019 there are 22737 visits with 17 services, 2019 reached 60417 visits with 20 services, until 2020 increased again to 100892 visits with 21 services. Thus the interest of patients using Prima HusadaHospital each year has increased.This study aims to analyze the factors that influence patients in utilizing outpatient services at Hospital of Prima Husada, which consists of hospital facility variables, physician services, nursing service or midwife, service fee, ease of information, and service utilization decisions.This research type is quantitative research with Cross Sectional design. Sampling technique with Stratified Random Sampling. The number of samples in this study is 100 respondents. Data collection using questionnaire instrument. Data were analyzed by SPSS with Chi-Square statistic test. Chi-Square analysis showed that there were correlation between hospital facility variable (p=0,004), physician service (p=0,033), nurse service or midwife (p=0,011), ease of information (p=0,001) with service utilization decision.The advice given is to maintain and provide the best service, should the hospital continue to make improvements on the availability of facilities, type, or variety of health services more complete.